ANALISIS ALOKASI BIAYA BERSAMA UNTUK PENENTUAN HARGA POKOK PRODUKSI PADA LIDYA CAKE AND BAKERY MANADO - Sepang, Gloria; Ilat, Ventje; Maradesa, Djeini (Universitas Sam Ratulangi, 2021)
Micro, Small and Medium Enterprises (MSMEs) is a type of business that is classified as simple. However, MSMEs must also pay attention to the amount of cost incurred to produce a product that is useful for determining the cost of production. Joint costs are costs incurred from the time the raw materials are first processed until the various products can be identified. This study aims to determine the calculation of the cost of goods manufactured by Lidya Cake And Bakery and analyze the calculation of the cost of production using the joint cost allocation method and then compare the calculation of the cost of production carried out by Lidya Cake And Bakery with calculations using the joint cost allocation method. Lidya Cake And Bakery is a cake shop business where bread products are the main product and are sold in several flavors. The type of research used is descriptive qualitative. The method of data collection is by conducting observations, interviews, and documentation. The results showed that the calculation of the cost of production with the allocation of joint costs obtained lower results than the calculations carried out by Lidya Cake And Bakery.